2000
DOI: 10.1097/00000658-200008000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hilar Cholangiocarcinoma

Abstract: In both Lahey and Nagoya patients, survival was most favorable when resection of hilar cholangiocarcinoma was accomplished with margin-negative resections. Combined bile duct and liver resection with caudate lobectomy contributed to a higher margin-negative resection rate in the Nagoya cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(42 citation statements)
references
References 30 publications
0
40
2
Order By: Relevance
“…However, cancer‐free resection margins at the bile duct stump are difficult to achieve because of longitudinal extension, which is one of the prominent characteristics of extrahepatic cholangiocarcinoma 11, 12. Ductal resection margin status is an established prognostic indicator,13, 14 and survival following resection in patients with positive ductal margins has generally been deemed unsatisfactory 10, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25. In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not.…”
Section: Introductionmentioning
confidence: 99%
“…However, cancer‐free resection margins at the bile duct stump are difficult to achieve because of longitudinal extension, which is one of the prominent characteristics of extrahepatic cholangiocarcinoma 11, 12. Ductal resection margin status is an established prognostic indicator,13, 14 and survival following resection in patients with positive ductal margins has generally been deemed unsatisfactory 10, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25. In 2005, Wakai et al26 reported that invasive carcinoma at the ductal resection margins had a strong adverse effect on survival in patients with extrahepatic cholangiocarcinoma, whereas residual carcinoma in situ did not.…”
Section: Introductionmentioning
confidence: 99%
“…2 Surgery provides the only chance for cure with varying resectability rates of 25-91% depending on tumour location. [3][4][5][6] However, obtaining a negative resection margin (RM) is a challenge, 7,8 and microscopic (R1) and macroscopic (R2) residual diseases are observed in 20-40% and 4-64%, respectively. [9][10][11][12][13][14][15] Many studies have revealed that positive RM of EHBD cancer is directly associated with high local recurrence (LR) rate.…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with those reported in other studies. 3,25 The concept of the importance of caudate lobe resection in association with hepatectomy in HCCA patients was adopted in recent years as it usually infiltrated with the tumors varying from 48% to 96%. 11,27 The value of this resection is now accepted, with a 5-year survival rate of 46% in those patients who underwent caudate lobe resection in comparison with 12% in patients without caudate lobe resection.…”
Section: Discussionmentioning
confidence: 99%
“…20,28 Most publications advise lymph node dissection at the porta hepatis and around the hepatic artery for staging and disease control. 3,2,29 Our policy was to start with lymph node dissection at the celiac trunk, common hepatic artery, retero-duodenal and porta hepatis. In the literature, different studies have shown that the 5-year survival rate in patients with lymph node metastasis does not exceed 25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation